The Pandemic - The Disease of the Underground Economy - Nitu, Alin Sergiu; Constantin, Marcel (Acta Universitatis Danubius. Œconomica, 2022)
In the current international pandemic context, the risks of the underground economy through its most perverse forms, corruption, undeclared work, tax evasion, etc., have been greatly exacerbated by urgently favouring the restriction of freedoms, the infusion of important resources into the economy and not least the interest of Pharma. The turbulent and unprepared international framework has created the premise that in this unfortunate period an activity in the underground economy that influences all its forms, namely corruption, will flourish. According to press reports, the sale of masks, medicines and anti-pandemic health products was a real El Dorado of Romania. Fabulous surcharge purchases made by UNIFARM are known, as well as worldwide, according to a World Bank report, due to the elimination of normal public procurement control filters. The pandemic generated by the SARS-CoV-2 virus, both globally and nationally, has had various influences on the underground economy, some favorable for the public sector but most unfavourable for the private sector.